Environmentální myšlenky v počátcích českého územního plánování - Dostalík, Jan (Lidé města, 2011)
This article revisits the theoretical beginnings of Czech town and country planning, and signifies its close relationship with contemporary environmental approaches. The essay focuses on the period between 1918 and 1949, and the basic situation in the development of the Czech theory of spatial planning. The article also points out the changes in the perception of the tasks of planners, and the change that urbanism underwent on the path from "the town to countryside". This text is based on the detailed analysis of contemporary texts by the most significant Czech architects, town planners, construction engineers and natural scientists. The first part introduces the most important trends in the world architecture of the late 19th and early 20th century, which most probably influenced Czech architecture. The article then focuses on the situation in Czech urbanism and spatial planning in the first half of the 20th century. The main part of the text is constituted by the introduction and evaluation of individual "environmentally thinking" authors and their approach, which hopefully helps to reveal the general approach in this sphere throughout the first half of the 20th century.